2013
DOI: 10.1007/s11356-013-1834-3
|View full text |Cite
|
Sign up to set email alerts
|

Levels, compositions, and inventory of polybrominated diphenyl ethers in sewage sludge of Guangdong Province, South China

Abstract: Polybrominated diphenyl ethers (PBDEs) were measured in sewage sludge samples collected from major wastewater treatment plants in Guangdong Province, South China. Concentrations of ∑ 39 PBDE (all 39 compounds including tri-to hepta-PBDE congeners except for BDE-209) ranged from 3.6 to 428 ng/g dw with a mean value of 67.4 ng/g dw and a median value of 25.9 ng/g dw, and those of BDE-209 ranged from 9.9 to 5,010 ng/g dw (mean 1,024 ng/g dw and median 824 ng/g dw). The PBDE mixtures detected were mainly comprised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Antibiotics are a group of emerging OCs that have received considerable attention in recent years. Alkylphenol polyethoxylates (APEOs), ,− bisphenol analogs (BPAs), ,,,, hormones, ,, ,− OCPs, ,,,,− PFCs, , pharmaceuticals, ,, ,,,, phthalate esters (PAEs), ,− PBDEs, ,− PCBs, ,,,,,,,− SMs,...…”
Section: Resultsmentioning
confidence: 99%
“…Antibiotics are a group of emerging OCs that have received considerable attention in recent years. Alkylphenol polyethoxylates (APEOs), ,− bisphenol analogs (BPAs), ,,,, hormones, ,, ,− OCPs, ,,,,− PFCs, , pharmaceuticals, ,, ,,,, phthalate esters (PAEs), ,− PBDEs, ,− PCBs, ,,,,,,,− SMs,...…”
Section: Resultsmentioning
confidence: 99%
“…PC2 was dominated by BDE-209, accounting for 22.83%. Therefore, PC1 and PC2 in Wet_SPM represented components of penta-and deca-BDEs, which is similar to the composition in e uent of wastewater treatment plants (WWTPs) (Ran et al, 2013). It was found that wastewater produced by enterprises in this area, such as electronic equipment manufacturing, plastic products processing and printing factories (Table S3), still contained residual PBDEs, which will be discharged into the tributaries and then carried into the reservoirs.…”
Section: Source Apportionment Of Pbdesmentioning
confidence: 78%
“…It was found that wastewater produced by enterprises in this area, such as electronic equipment manufacturing, plastic products processing and printing factories (Table S3), still contained residual PBDEs, which will be discharged into the tributaries and then carried into the reservoirs. In fact, removal rate of PBDEs in Hong Kong WWTPs was 20 ~ 52% (Deng et al, 2015), and e uent of Guangzhou WWTPs contained a small amount of PBDEs (0.9 ~ 4.4 ng/L), while PBDEs in sludge of Shenzhen WWTPs reached up to 500 ng/g (Ran et al, 2013). All these proved considerable concentrations of PBDEs in e uents of WWTPs that should be one of the important sources of PBDEs in reservoirs.…”
Section: Source Apportionment Of Pbdesmentioning
confidence: 94%